Brake discs: A technological review from its analysis and assessment (2019)
Braking systems are undoubtedly the most important component for road safety, since it determines the total or partial stop of a vehicle and, therefore, guarantees the physical integrity of passengers. Normally, the front brake discs and the remaining percentage absorb 70% of the kinetic energy produced within a vehicle by the rear brake discs, which tend to have the formof a drum brake. These systems benefit from friction to stop a moving vehicle, under the umbrella of hydraulic pressure that pushes the brake pads against the iron-cast disk. In this document, concepts of famous authors around the world on analysis and evaluation of brake discs are provided, which are carried out using a descriptive methodology and an estimation of the characteristics of the brake disc. The review is carried out in computer assisted design through several existing CAD software in the industry, as the main methodology applied to the development of certain research projects, where different geometric characteristics of the brake discs are considered, as well as problems related to wear and corrosion. This research project has shown that it is vital to incorporate existing computer assisted design software to predict performance, improve components and optimize the functionality of the brake system. In this way, road traffic safety and systems efficiency are achieved, which are a matter of great importance for the industry. It is vital to analyze brake systems through Finite Element Analysis (FEA), with the intention of achieving a broader vision of its performance, since the information collected reveals that the geometric characteristics of the brake and cooling ducts influence the heat dissipation. It depends on the form, the type of material and the application, the heat generated between the pad and the brake. Therefore, the heat is dissipated rapidly according to the analysis performed mathematically by the researchers, which are compared with the made in computer assisted design software.